Contribution of Generative AI to Creativity: - Makoto Ogawa; Yutaka Oguchi; Ayaka Chida (Maketingu Janaru, 2024)
This paper discusses how generative AI can contribute to human creativity. We conducted a review of creativity research in marketing, psychology, and cognitive science to examine the behaviors and processes that create human creativity, and developed a hypothesis based on similarities with the mechanism of generative AI. Three hypotheses were developed and tested: (1) use of generative AI contributes to the creativity process, (2) step-by-step presentation of information created by generative AI contributes to creativity, and (3) creative entities with greater expertise in the task are more likely to use generative AI and demonstrate creativity. We prepared a total of 12 designs, 6 with AI and 6 without AI, and conducted expert interviews with three package designers, a quantitative survey of 85 package designers, and a user survey of 200 users. The results of the user survey showed that the generative AI contributed to creativity. In contrast, the quantitative survey of 85 package designers showed no contribution to creativity from the step-by-step provision of information. The quantitative survey also indicated that generative AI improves creativity for designers with less experience, whereas for designers with more experience, AI-generated images contribute to creativity even if they are distant from the objective.